Poverty among the Elderly in Latin America and the Caribbean - Leonardo Gasparini; Javier Alejo; Francisco Haimovich; Sergio Olivieri; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2007)
This paper provides evidence on the incidence of poverty among the elderly in Latin America and the Caribbean, based on household survey microdata from 20 countries. The situation of older people is characterized in terms of income, employment, education, health and access to services vis-à-vis the rest of the population. The paper identifies the role played by the current pension systems in Latin America, and assesses the efforts needed to achieve substantial improvements toward the reduction of old-age poverty.
Keywords: D3; I32; O54; 330; elderly; ageing; poverty; Latin America; Caribbean